Prevalence of electronic device use before bed among Australian children and adolescents: a cross‐sectional population level study - Mary E. Brushe; Tamina Islam; Neida Sechague Monroy; Alanna Sincovich; Tess Gregory; Amy Finlay‐Jones; Sally A. Brinkman (Elsevier, 2022)
Abstract Objective: To understand the prevalence of children and adolescents' electronic device use (EDU) in the hour before bed and identify sociodemographic groups that are at increased risk of problematic use. Method: A contemporary population wide sample of South Australian school students aged 8‐18 years (n = 70,936) was utilised to present descriptive statistics of EDU before bed across sociodemographic groups. Data was collected from the 2019 Wellbeing and Engagement Collection, an annual self‐report census of students' health, wellbeing and school engagement. Results: 90% of children used an electronic device in the hour before bed at least one night a week, with 51% using a device every night. Older adolescent females in grades 10‐12 were most frequent users and children from the most socioeconomically disadvantaged communities were also more likely to use electronic devices in the hour before bed. Conclusion: EDU before bed is highly prevalent among Australian children and adolescents and given the negative health and educational impacts, it requires immediate and widespread action from policy makers to ensure the health of Australia's next generation. Implications for public health: The scale of the problem has now been identified; next steps rely on a public health approach to address this issue. This might include awareness raising campaigns and targeted interventions towards at‐risk groups.